2001
DOI: 10.1021/jp0042462
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition Pathways and Rates for Dimethylaluminum Hydride

Abstract: Calculations have been carried out for the thermal decomposition of dimethylaluminum hydride (DMAlH). For each decomposition pathway, the stationary point geometries and harmonic frequencies were characterized using complete active space self-consistent field (CASSCF)/derivative methods and the correlation consistent polarized valence double-ζ (cc-pVDZ) basis set. Accurate energetics were obtained by combining the coupled cluster singles and doubles with perturbational estimate of triples [CCSD(T)] results usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The CCSD(T) method used here is a single reference based method, but this method has been shown to deal with all but the most severe near-degeneracy effects. In a recent paper, we showed that for the decomposition of dimethylaluminum hydride CCSD(T) gave results in good agreement with the multireference internally contracted CI method …”
Section: Computational Detailsmentioning
confidence: 85%
“…The CCSD(T) method used here is a single reference based method, but this method has been shown to deal with all but the most severe near-degeneracy effects. In a recent paper, we showed that for the decomposition of dimethylaluminum hydride CCSD(T) gave results in good agreement with the multireference internally contracted CI method …”
Section: Computational Detailsmentioning
confidence: 85%
“…Thermochemistry of the methylene-benzene reaction sum of ∆H f ( 1 CH 2 ) and ∆H f (benzene) by 37 kJ/mol, it was concluded that X must be a methylene-benzene complex. However, ∆H f values for CH 2 N 2 have been computed (285 and 281 kJ/mol) [107][108] that exceed Goodman's. On the product side, the isomerization of norcaradiene to give cycloheptatriene (k 298 ഠ 10 7 s Ϫ1 ) [109] may not be complete on the time scale of the calorimetric experiment.…”
Section: Arenesmentioning
confidence: 99%